The Trend of The Green Human Resources Management and its Impact on The Creativeness in The Industrial Sector in Sudan - Al- Taher, Sana Jadallah Al- Sheikh; Abu Sen, Ahmed Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2019)
The main goal of this study was to know the impact of the trends of the green human resources management on the creativeness in the industrial sector in Sudan. Based on the human resources theory,the study model was constructed and hypotheses were deducted and tested by a non- probability sample comprised of 330 employees in the industrial sector. The findings showed a reverse relationship between the trends of the green human resources management and creativeness of employees. One of the applied study core was to assist decision- makers to understand the best way for the trends of the green human resources management. The study recommended that the future studies should be conducted on the relationship between the trends of the green human resources management and creativeness.